PEDAGOGICAL FEATURES OF THE DEVELOPMENT OF CREATIVITY IN PRIMARY SCHOOL AGE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Creativity is understood as an ability that reflects the deep property of individuals to create original values and make non-standard decisions. The author refers to this concept in connection with the fact that the main requirement for education today is the development of a creative personality capable of going beyond the known, making non-standard decisions, creating products characterized by novelty. Psychologists, when characterizing creativity, point to the problem of abilities and most often creativity is considered as a general creative ability, the process of transformation of knowledge.